Effect of body mass index on functional outcomes following arthroplasty procedures - Polat, Gokhan; Ceylan, Hasan Huseyin; Sayar, Safak; Kucukdurmaz, Fatih; KÜÇÜKDURMAZ, FATİH; Erdil, Mehmet; TUNCAY, İBRAHİM; TUNCAY, İBRAHİM (My University, 2015)
AIM: To evaluate the body mass index (BMI) change in arthroplasty patients and its impact on the patients- functional results.
Keywords: body mass index